Mental Health Communication; Prevention Efforts Against Stunting in Bangsalsari Village - Riskha Dora Candra Dewi (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This service is carried out to provide education and prevention of stunting growth in Bangsalsari village through strengthening health communication about mental health for pregnant women. this service was carried out on 28-29 June 2024 at the PKK room at the Bangsalsari village office involving participants from various groups of village residents. the service was carried out for two days starting at 08.00 WIB. the service was carried out by presenting several education courses regarding health and stunting, especially regarding mental health communication with its influence on stunting and its growth. this activity is an effort to educate oneself in controlling the mental health faced by pregnant women and children in Bangsalsari adults. implementing effective communication with all existing communication media devices is part of ensuring that communication runs effectively so that counseling through effective communication can at least reduce the possibility of mental health problems.